The approach of tafakkur in sirah education - Tengku Nor Husna Tengku Jamil,; Hasanah Abd Khafidz,; Khazri Osman, (Pusat Kesejahteraan Insan dan Komuniti, Universiti Kebangsaan Malaysia, 2018)
The approaches of da'wah play an important role in Islamic education. Various approaches can be used in educating the students. Sirah education requires a special approach to provide the students with the ability to remember and emulate the taught knowledge in life, until it leads to the process of emulation as emphasized in the Islamic education curriculum in Malaysia. Therefore, through the concept of reflection that is mentioned in the Quran, the tafakkur approach is very relevant to be applied in da'wah education. Teachers of Islamic education as dais will not be only bound with the traditional approaches and should not necessarily evaluate the students based on their excellence in examinations. Through a qualitative study that followed an analytical method, the current research paper examines the tafakkur approach in the education of sirah. The current study is important to ensure that the sirah education is favoured more, delivered it to the souls, and touches the heart of the student and the mad'us. The findings show that by looking forward to Allah’s pleasure, linking the chain of events, and understanding the moral are appropriate tafakkur approaches that fulfils the aspects stated in the Qur'an.